The Concept Of Sharia Finance That Is An Islamic Microfinance Institution - Latifah, Eny; Paulina, Ningsih (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2019)
The purpose of this study was to determine the extent of the concept of existing financial statements Islamic Microfinance Institution precisely in the Cooperative Savings and Loans Coordination of Sharia Islamic Education Ummah Lamongan. The research method uses a qualitative approach that is descriptive in order to get a clear picture of the use of sharia accounting in the Islamic Microfinance Institution, which is precisely in the Savings and Loan Co-operative for the Development of Sharia Bina Syariah Ummah Lamongan. The results of this study are the concept of financial statements presented by Islamic Microfinance Institution Bina Syariah Ummah Lamongan is more referring to SAK ETAP. Financial statements that include a balance sheet, income statement, statement of changes in financial position that can be presented in various ways, such as cash flow statements and cash flow statements, notes and other reports. Because Islamic Microfinance Institution Bina Syariah Ummah Lamongan needs an adjustment process to provide financial reports with sharia accounting approaches because of the transfer of labels from Conventional financial institutions to Islamic financial institutions.